Student engagement with digital video production. (27th August 2021) - Henry, Alastair
Abstract: In many contexts of contemporary ELT, the L2 can be widely encountered beyond the classroom. In these settings, teachers need to maximize opportunities for meaningful participation. Digital video production (DVP) provides one such opportunity. Little, however, is known about the types of DVP common in particular contexts of ELT, the extent to which DVP functions as a motivational resource, or how engagement is generated. This mixed-methods study in a Swedish context addresses these questions. Results show that DVP takes place in genre-specific forms and has significant motivational potential. Analyses suggest that DVP can generate embodied forms of engagement. By creating appealing characters and storylines, and through the use of mobile devices and easy-to-use video-editing software, students can engage in authentic self-expression in meaningful and satisfying ways. Insights into the ways in which engagement is generated can provide teachers with valuable knowledge when designing learning activities that incorporate DVP.